Pengaruh Kualitas Produk dan Kualitas Jasa Terhadap Kepuasan Konsumen Di Cyrano Café - Yusrifah Justi Akhita; Abdul Basith; Ma'mun Sarma (Jurnal Manajemen Pembangunan Daerah, 2025)
ABSTRACT Cyrano Café is one of the restaurants in the city of Bogor. The rapid growth of culinary business increases competition in attracting consumers. Cyrano Café must increase efforts to give customers satisfaction and interest in repurchasing. The purpose of this study was to identify consumer characteristics, analyze the effect of product and service quality on customer satisfaction, analyze the influence of product and service quality on repurchase interests, analyze the effect of customer satisfaction on consumers; repurchasing interest at Cyrano Café. The sampling technique used the purposive method with a sample of 100 respondents. Data were analyzed descriptively and analytically using Structural Equation Modeling (SEM) analysis with SmartPLS software. The results of the analysis show that product quality and service quality have a positive and significant influence on customer satisfaction and repurchase interest. This shows that the better the quality of the product and the quality of service, the better customer satisfaction and satisfied consumers have the desire to repurchase. Keywords: Consumer Satisfaction, Product Quality, Repurchase Interest, Service Quality